2016
DOI: 10.12738/estp.2016.2.0390
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Results of Many-Facet Rasch Analyses Based on Crossed and Judge Pair Designs

Abstract: Citation: İlhan, M. (2016). A comparison of the results of many-facet Rasch analyses based on crossed and judge pair designs. AbstractThe aim of this study was to compare the results of many-facet Rasch analyses based on crossed and judge pair designs. The study was conducted with 168 eighth grade students and five judges. The study data were collected using an achievement test with open-ended questions and a holistic rubric that was used to rate the responses. In the data collection process, the achievement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Implementing a crossed or mixed design can be time consuming, costly, and result in rater fatigue when rating a large number of students' responses. Also, research conducted by Ilhan (2016) demonstrated that resultant student measures were highly consistent across the two design types applied to the same data set consisting of 168 eighth-grade students, five judges, and ten CR items applying the many-faceted Rasch model. It is recommended to adopt the judge-pair design for when judging a large number of responses such as in the current study (Boone et al, 2016).…”
Section: Author Manuscriptmentioning
confidence: 90%
“…Implementing a crossed or mixed design can be time consuming, costly, and result in rater fatigue when rating a large number of students' responses. Also, research conducted by Ilhan (2016) demonstrated that resultant student measures were highly consistent across the two design types applied to the same data set consisting of 168 eighth-grade students, five judges, and ten CR items applying the many-faceted Rasch model. It is recommended to adopt the judge-pair design for when judging a large number of responses such as in the current study (Boone et al, 2016).…”
Section: Author Manuscriptmentioning
confidence: 90%